Prevalence of osteo-renal impairment in the Romanian HIV cohort. Issue 1 (March 2016) - Streinu-Cercel, Anca; Săndulescu, Oana; Ceapraga, Gabriela; Manolache, Daniela; Stoica, Monica; Preoțescu, Liliana; Streinu-Cercel, Adrian
Abstract Background The Romanian HIV cohort has certain particularities that render it unique in Europe. We have performed a study to evaluate the prevalence of bone and kidney impairment in this particular group of HIV-infected patients. Methods We performed dual-energy X-ray absorptiometry (DXA) evaluation of the lumbar vertebrae and the femur, as well as laboratory tests including standard serum panels, bone-related markers and urinalysis in patients from the Romanian HIV cohort. Results The study included 72 patients, of which 46 (58.3 %) were males. The median (IQR) age was 38 (18) years and the median (IQR) time from HIV infection diagnosis was 9 (13) years. Most patients (55.6 %) were non-smokers, but a relatively high proportion (37.5 %) was currently smoking. Only a small percentage of patients (20.8 %) did not present any comorbidities, while 40.3 % had one comorbidity, the most frequent being dyslipidemia (present in 25 patients, 38.5 %). Only 6 patients had a medical history suggestive for renal disease and 3 for bone-related abnormalities. The median (IQR) glomerular filtration rate was 97.5 (33.0) mL/min/1.73sqm. We diagnosed 21 patients (29.6 %) with stage 2 chronic kidney disease and one patient (1.4 %) with stage 3 chronic kidney disease. Proteinuria was present in 9 (12.7 %) patients. The estimated glomerular filtration rate was significantly lower in patients with cardiac comorbidities (p  = 0.013). Vitamin D was significantly lower in smokers compared with non-smokers, with a mean value of 15 vs. 21 ng/mL and a moderate effect size (Cohen's d = −0.5) (p  = 0.046). Lumbar osteopenia and osteoporosis were diagnosed in 33.3 and 13.7 % of patients, while femoral osteopenia and osteoporosis were diagnosed in 37.3 and 7.8 %, respectively. Lower nadir CD4 cell counts were found in patients with bone-related comorbidities (p  = 0.000). Conclusions We identified a relatively high prevalence of chronic kidney disease in the Romanian HIV cohort, and a fairly low prevalence of osteopenia and osteoporosis, compared with other European countries. In this category of patients smoking should be avoided altogether, as it may be an indirect risk factor for kidney disease (associating cardiac comorbidities) and it may impair bone metabolism by altering serum levels of hydroxy-vitamin D.